What is the background for the histological diagnosis of autoimmune pancreatitis?. Issue 7 (30th December 2020) - Kanno, Atsushi; Lefor, Alan Kawarai; Yamamoto, Hironori
Abstract : This Editorial refers to the article by S.B. Yoon et al., p 1024‐1033 of this issue.